2016
DOI: 10.1039/c5cp07468a
|View full text |Cite
|
Sign up to set email alerts
|

Specific ion modulated thermoresponse of poly(N-isopropylacrylamide) brushes

Abstract: The influence of specific anions on the equilibrium thermoresponse of poly(N-isopropylacrylamide) (pNIPAM) brushes has been studied using in situ ellipsometry, quartz crystal microbalance with dissipation (QCM-D) and static contact angle measurements between 20 and 45 °C in the presence of up to 250 mM acetate and thiocyanate anions in water. The thickness and changes in dissipation exhibited a broad swelling transition spanning approximately 15 °C from collapsed (high temperatures) to swollen conformation (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
110
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(124 citation statements)
references
References 54 publications
13
110
1
Order By: Relevance
“…The Tonset corresponded well with the temperature of the heat‐induced dehydration and collapse of PNIPAAM brushes at planar surfaces. In such a brush, the outermost polymer segments are solvated until about 32 °C, while the densely packed segments within the brush undergo a dehydration and collapse to a rigid conformation over a broad temperature range, which can span up to 20 °C . In contrast, Tonset of the PNIPAAM 30 homopolymer studied here was higher in comparison (38.6 °C), so that LCST is elevated in this case.…”
Section: Resultsmentioning
confidence: 72%
“…The Tonset corresponded well with the temperature of the heat‐induced dehydration and collapse of PNIPAAM brushes at planar surfaces. In such a brush, the outermost polymer segments are solvated until about 32 °C, while the densely packed segments within the brush undergo a dehydration and collapse to a rigid conformation over a broad temperature range, which can span up to 20 °C . In contrast, Tonset of the PNIPAAM 30 homopolymer studied here was higher in comparison (38.6 °C), so that LCST is elevated in this case.…”
Section: Resultsmentioning
confidence: 72%
“…As a result, in the last years several experimental and numerical studies have been carried out to investigate PNIPAM chains and microgels solution behavior [1,10]. The LCST/VPTT control can be achieved by variations of chemical [11] and stereochemical [12,13,14] composition of the polymer and by variations of the aqueous suspension medium, concerning ionic strength [15,16,17] and cosolute [18,19] or cosolvent addition, the latter being one of the simplest and less expensive ways to decrease the transition temperature [20,21,22]. In particular, the presence of ethanol as water cosolvent has a drastic impact on PNIPAM solution behavior, since this polymer, soluble in ethanol at all temperatures and in water at T ≤ 305 K, is actually insoluble in ethanol/water mixtures having an ethanol mass fraction approximately from 20% to 60%, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2 ) on the equilibrium thermoresponse of PNIPAAm brushes was studied using in situ ellipsometry, quartz crystal QCM-D, static contact angle measurements, neutron reflectometry (NR), and AFM [31,32]. It was found that the shift in transition temperature was in line with the Hofmeister series where transition temperature was shifted to lower temperature by kosmotropic acetate ions and higher temperature by chaotropic thiocyanate ions [31,32].…”
Section: The Effect Of Specific Anions (Scn − and Ch 3 Co −mentioning
confidence: 99%
“…2 ) on the equilibrium thermoresponse of PNIPAAm brushes was studied using in situ ellipsometry, quartz crystal QCM-D, static contact angle measurements, neutron reflectometry (NR), and AFM [31,32]. It was found that the shift in transition temperature was in line with the Hofmeister series where transition temperature was shifted to lower temperature by kosmotropic acetate ions and higher temperature by chaotropic thiocyanate ions [31,32]. Koenig et al studied the effect of NaCl salt on the thermoresponsive behavior of PNIPAAm brushes using QCM and ellipsometry and found that transition temperature was shifted to lower temperatures by the addition of NaCl salt due to the interaction of the ions with the amide groups and the hindrance of hydrogen-bonding formation [33].…”
Section: The Effect Of Specific Anions (Scn − and Ch 3 Co −mentioning
confidence: 99%
See 1 more Smart Citation